KEPUASAN KONSUMEN TERHADAP PELAYANAN APOTEK DAN TINGKAT PENGETAHUAN KONSUMEN MENGENAI STANDAR PELAYANAN KEFARMASIAN YANG BERLAKU (STUDI KASUS DI KOTA DEPOK) - Prima Roza Yulia; Lukman M. Baga; Setiadi Djohar (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2016)
Customer satisfaction is one of the indicators in the success of business services, including the health services such as pharmacy. Customer satisfaction towards pharmaceutical services can be measured by comparing customer expectation towards service quality in reference to the experienced reality of service performance. The objectives of this study are to analyze customer satisfaction and expectation levels, as well as to examine the prioritized improvement attribute in the pharmaceutical service dimension in Depok City. Moreover, it also aims to reveal the level of customer knowledge in Depok City towards pharmaceutical service standard in pharmacies, in accordance with what is established by the government. Analytical method in this research was performed by applying gap analysis in reference to the concepts of Service Quality (Servqual), Customer Satisfaction Index/CSI, and Importance Performance analysis (IPA).The results of the study showed that customer satisfaction towards the quality of pharmaceutical services in Depok City is still in the ‘adequate’ category but still below the ‘satisfied’ category. Meanwhile, the prioritized service attributes to be improved include the presence of pharmacists in pharmacies, availability of medicinal drugs, and feedbacks from pharmacists on customer questions regarding the medicines they purchase. On the other hand, the respondents’ knowledge on pharmaceutical services in pharmacies, in accordance with the standard established by the government, is still lacking.Keywords: pharmacy, customer satisfaction, pharmaceutical services, servqual, IPAABSTRAKKepuasan pelanggan merupakan salah satu indikator dari keberhasilan layanan bisnis, termasuk juga pada pelayanan kesehatan seperti apotek. Kepuasan pelanggan terhadap pelayanan apotek dapat diukur dengan membandingkan harapan pelanggan terhadap kualitas layanan dengan kenyataan dari kinerja layanan yang  diterima. tujuan penelitian ini adalah menganalisis tingkat kepuasaan dan harapan konsumen serta prioritas perbaikan atribut pada dimensi pelayanan apotek di Kota Depok Selanjutnya, untuk mengetahui tingkat pengetahuan konsumen di Kota Depok terhadap standar pelayanan kefarmasian di apotek, sesuai dengan yang ditetapkan pemerintah. Metode analisi dalam penelitian ini menggunakan analisis gap berdasarkan konsep Service quality (Servqual), Indeks Kepuasan Pelanggan (Costumer Satisfaction Index/CSI) dan Importance Performance analysis (IPA). Hasil penelitian menunjukkan bahwa kepuasan pelanggan untuk kualitas pelayanan apotek di Kota Depok adalah dalam kategori 'cukup' tapi masih di bawah kategori 'puas'. Sementara atribut pelayanan yang diprioritaskan untuk perbaikan adalah: kehadiran apoteker di apotek, kelengkapan obat, dan tanggapan dari petugas apotek atas pertanyaan konsumen mengenai obat-obatan yang mereka dapatkan. Di sisi lain, pengetahuan responden tentang pelayanan kefarmasian di apotek yang sesuai dengan standar yang ditetapkan oleh pemerintah masih kurang.Kata kunci: apotek, kepuasan konsumen, pelayanan kefarmasian, servqual, IPA